Experience of a Childbirth Mother Assisted by Shaman Paraji: A Phenomenology Study in Sumber Lor Village, Babakan Sub-District, Cirebon Regency - Fitria Prihatini; Adi Fahrudin; Irna Nursanti (Asian Social Work Journal, 2019)
In Cirebon District the percentage of women giving birth was helped by health workers as much as 91.7%, while the remaining 8.3% was helped by health workers. In Sumber Lor, Babakan, the number of women giving birth in 2016 was 121 people. The results of interviews with traditional birth attendants that women were helped in 2016 amounted to 6 people. This study aims to explore the meaning and meaning of the mother's experience giving birth helped by the paraji shaman in Sumber Lor Village, Babakan Sub-district, Cirebon District. This study uses a phenomenological study approach. Subjects in this study were 7 women who gave birth assisted by a traditional birth attendant. Traditional birth attendant 2 and husband of 6 people as supporting participants. The results obtained in the study of maternal experience were helped by the paraji shaman in the village of Sumber Lor, Babakan Subdistrict, Cirebon Regency, which is the reason that some people still choose the paraji shaman as their birth attendant with a paraji dukun because these women want labor done at home (homebirth), The other is the cause of some people who still want to be helped by a traditional birth attendant because they feel comfortable giving birth by a traditional birth attendant, and the paraji shaman does a complete and caring service until the mother recovers and the baby's belly button is cured. Family support is one of the factors why maternity is assisted by traditional birth attendants, patience of traditional birth attendants when helping, and trust in the shaman, the assumption of the community to the midwife and midwife is the same as helping mothers give birth. The simple thinking of the community, which is important to survive during childbirth, makes them believe and believe in the paraji shaman and the cheap and complete costs are also a motivation for mothers who give birth.